2018
DOI: 10.1007/s13181-018-0674-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Benzodiazepine by Heroin Users—What Are the Prevalence and the Risks Associated with This Pattern of Use?

Abstract: This study shows that co-use of heroin and benzodiazepines is common, although the overall outcomes between co-users of heroin and benzodiazepines and heroin-only users were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…35,36 Data from the Euro-DEN dataset is collected from sentinel centres rather than all emergency departments across the countries, although they are primarily located in large cities that are associated with high-levels of recreational drug use. 37 There was variability in number of tramadol related acute toxicity related presentations across the Euro-DEN Plus centres with clustering of cases in certain countries. These presentations potentially pose a significant burden on EDs with a large proportion requiring admission to hospital for ongoing care.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Data from the Euro-DEN dataset is collected from sentinel centres rather than all emergency departments across the countries, although they are primarily located in large cities that are associated with high-levels of recreational drug use. 37 There was variability in number of tramadol related acute toxicity related presentations across the Euro-DEN Plus centres with clustering of cases in certain countries. These presentations potentially pose a significant burden on EDs with a large proportion requiring admission to hospital for ongoing care.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Combining opioids and sedatives increases the risk of respiratory depression, overdose and death. 7,8,35 While data regarding co-use of Z-drugs and prescription opioids are limited, it has been suggested that the main attractions of zopiclone for drug users is that, unlike benzodiazepines, they do not cause amnesia and may not be detected during standard illicit drug screening. 36,37 Acquisition of benzodiazepines/Z-drugs for NMU was more common without a prescription than with a prescription and obtaining the drugs from family/friends was the most common source of acquisition for both drug groups.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, a cause for concern is concurrent use of benzodiazepines by heroin users and increased risk of emergency department visits, overdose and death. 7,8 The available data suggest that benzodiazepines encountered on the illicit drug market are primarily diverted from legitimate sources rather than being counterfeit medicines and that diversion can occur at all points along the pharmaceutical supply pathway from manufacturing sites and distributors to patients themselves. 4 A 2016 report by the UK Advisory Council on the Misuse of Drugs on Diversion and Illicit Supply of Medicines found that within the UK the most prevalent diverted drugs are opioids and benzodiazepines, with benzodiazepines and Z-drugs being the most common medicines illegally diverted from the regulated supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing problem with high dose BZD dependence both internationally and in Dublin ( Darker, Sweeney, Barry & Farrell, 2015 ; Yamamoto et al., 2019 ). Up to 66% of patients on OST misuse BZDs ( Nielsen, Dietze, Lee, Dunlop & Taylor, 2007 ).…”
Section: Bzd Maintenancementioning
confidence: 99%